Driving sustainable future with TVET - Norhidayah, Mohamad (2017)
The two days of UMP TVET Research Exhibitions held at UMP Gambang Sports Complex was a success when it gather nearly 100 researchers who share their ideas and thoughts to empower and strengthen Technical and Vocational Education Training (TVET) in this country.